Morphometry and comparative histology of sinus and atrioventricular nodes in humans and pigs and their relevance in the prevention of nodal arrhythmias. (February 2020) - Gómez-Torres, F.A.; Sebastian, R.; Ruíz-Sauri, A.
Abstract: The cardiac conduction system is a network structure that allows the initiation and fast propagation of electrical impulses that trigger the electrical depolarization of the myocardial tissue. The purpose of this work is to study the histological and morphometric characteristics of the different components of the sinus and atrioventricular nodes in humans and pigs and their relationship with supraventricular arrhythmias. In this study, we describe the morphometry of the sinus and atrioventricular nodes of 10 adult humans and 10 pig hearts. A computerized morphometric study has been carried out, where we determined the number of cells that compose the nodes as well as different parameters related to their shape and size. The sinus node in human and pig is a compact structure, whose shape is oblong. Their cells (nodal and transitional cells) are pale and located in the center and the periphery, respectively. The atrioventricular node has also a shape oblong. P cells are pale in both species, but in humans, they are smaller than cardiomyocytes. The T cells are small and pale in both species, identified by hematoxylin-eosin and desmin stains. We have observed through a morphometric profile that the structure of sinus and atrioventricular nodes of pigs and humans show few differences. Pigs can be used as models for hemodynamic applications and experimental studies that include atrial electrical conduction and, in this way, prevent the presentation of arrhythmias that can generate sudden deaths in humans and pigs. Highlights: The cardiac nodes are composed mainly of connective tissue and their shape is oblong. In the cardiac nodes the P cells are round and the T cells are elongated. The sinus node in humans presents T cells organized linearly in the periphery. In the atrioventricular node in humans, P cells are smaller than myocardiocytes. In the atrioventricular node in pigs P cells are twice the size of myocardiocytes.